Appium(Selenium)-mobile automation testing from scratch - Shetty, Rahul (Packt Publishing, 2018)
"Learn everything you need to know about Mobile Automation (Android+ IOS) Even If you've never programmed before! I teach the concepts from the scratch assuming my students are new to automation and will get them through real time examples to boost confidence on them and finally make them ready for Interviews with my lectures. I have made one section on Selenium Webdriver basics for the students who do not have knowledge on Selenium. You can go through them to make your basics strong and switch back to Appium for better understanding. Topics include: Appium features Appium internal architecture configuration setup on your device working on native apps working on hybrid apps Appium API's explanation mobile gestures automation automating browser apps. Tips in identifying objects on App and browser automating on real devices: How to start with IOS IOS capabilities and guidelines Appium latest updates, Appium Integration with Maven Selenium Basics (optional). It's time to learn mobile automation! Mobile market is booming tremendously and need of quality testing in these platforms becoming a major challenge, especially finding a right automation tool which works on all mobile platforms. Major asset of Appium is that this can work on both Android and iOS platforms, which means write the code once and execute it in across platforms. All the topics were taught from basic to advanced level with a lot of tricks and tips which makes users to get perfection on the things. At the end of this course you can pick any mobile application and can automate it whatever the way you want."--Resource description page